2021
DOI: 10.1061/(asce)ps.1949-1204.0000566
|View full text |Cite
|
Sign up to set email alerts
|

Lateral and Uplift Capacity of Pipeline Buried in Seabed of Homogeneous Clay

Abstract: Buried offshore pipes are prone to upheaval and lateral buckling because of the high temperature and pressure of the materials being transported. An attempt has been made in the present study to evaluate uplift and lateral capacity of buried offshore pipes in a soft clay seabed using finite-element software. The numerical model used in the present study has been validated against results available in the literature. Finite-element analyses are carried out to study the upheaval and lateral buckling behavior of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
(54 reference statements)
2
3
0
Order By: Relevance
“…However, when H/D was greater than or equal to 2, a localized circumferential soil flow surrounding the pipeline occurred. This is consistent with the conclusions obtained by Kumar et al [4], which suggested that critical soil cover depth ratios for both the global and local failure modes was 2 for rough pipelines under full tension in uniform soils. Figures 4 and 5 depict the displacement contours and the corresponding soil's undrained strength distribution in the random soil with pipeline soil cover depth ratios of 0.5 and 1, respectively.…”
Section: Failure Mechanism In Deterministic and Random Soilsupporting
confidence: 93%
See 2 more Smart Citations
“…However, when H/D was greater than or equal to 2, a localized circumferential soil flow surrounding the pipeline occurred. This is consistent with the conclusions obtained by Kumar et al [4], which suggested that critical soil cover depth ratios for both the global and local failure modes was 2 for rough pipelines under full tension in uniform soils. Figures 4 and 5 depict the displacement contours and the corresponding soil's undrained strength distribution in the random soil with pipeline soil cover depth ratios of 0.5 and 1, respectively.…”
Section: Failure Mechanism In Deterministic and Random Soilsupporting
confidence: 93%
“…Furthermore, when the soil cover depth ratio H/D was less than 2, N u increased with the increase of H/D and reached a maximum value when H/D equaled 2 and remained constant as H/D increased, indicating a critical depth ratio for H/D = 2. According to the study of Kumar et al [4], in the case of a full tension condition, H/D = 2 is the critical depth ratio for a failure mechanism to transition from a global failure to a local failure. The results of this study also indicate this trend.…”
Section: Validation Of the Numerical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, it is observed by the other researchers that the behaviour of the piles under lateral displacement is similar to the behaviour of the pipelines under vertical displacement [54,56]. It is also found by the researchers that, for ideal cases (weightless soil and unlimited pipe-soil interface tension), the penetration resistance and uplift resistance [54,56,58,59] of the pipeline reached a peak value of 9.14 for smooth pipes and 11.94 for rough pipes. Several authors observed that soil strength is one of the crucial factors to influence the uplift resistance.…”
Section: Analytical Modelssupporting
confidence: 67%
“…For a buried pipeline, the uplift resistance of the pipeline is usually lesser than the lateral resistance and downward penetration resistance. Thus, the global uplift buckling is the predominant buckling criteria for a buried pipeline [49][50][51][52][53][54][55][56][57][58][59]. However, global lateral buckling was also analysed in some cases as they were believed to be crucial for the pipeline design.…”
Section: Buried Pipelinementioning
confidence: 99%